2019
DOI: 10.1136/vetreco-2019-000341
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological factors affecting the risk of transmission of HPAI in Miyazaki, Japan

Abstract: Highly pathogenic avian influenza (HPAI) outbreaks engender a severe economic impact on the poultry industry and public health. Migratory waterfowl are considered the natural hosts of HPAI virus, and HPAI viruses are known to be transmitted over long distances during seasonal bird migration. Bird migration is greatly affected by the weather. Many studies have shown the relationship between either autumn or spring bird migration and climate. However, few studies have shown the relationship between annual bird m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Although the ARMA model has good prediction performance, it only forecasts according to the historical incidence data and does not take into account some factors that may affect the incidence of the disease. Many studies have found that the infectious disease is related to air pollution variables [9][10][11][12][13]. Proper consideration of air quality factors can not only improve the accuracy of prediction, but also improve the scientific nature of prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ARMA model has good prediction performance, it only forecasts according to the historical incidence data and does not take into account some factors that may affect the incidence of the disease. Many studies have found that the infectious disease is related to air pollution variables [9][10][11][12][13]. Proper consideration of air quality factors can not only improve the accuracy of prediction, but also improve the scientific nature of prediction.…”
Section: Introductionmentioning
confidence: 99%